Effectiveness of Kabat therapy as a complement therapy in medical and physical therapy of Bell's palsy patients: Literature review: Efektivitas terapi Kabat sebagai terapi komplemen pada terapi medikasi dan terapi fisik pasien Bell’s palsy: Kajian pustaka - Hasmawati Hasan; Nurmagfirah Rafiuddin (Makassar Dental Journal PDGI Makassar, 2022)
Background: Almost 85% Bell's palsy patients will recover partially in 3-4 weeks and fully recover in 6 months. However, only 61% of patients with complete paralysis hade a full recovery. Of the patients who did not recover, sequelae were slight in 12% of patients, mild in 13%, and severe in 4%. Then, about 30% of those who are not treated will have a poor recovery, with continued facial disfigurement, psychological difficulties, and facial pain. Objective: To discusses the effectiveness of Kabat therapy as a complement therapy in the medical therapy and physical of Bell's Palsy patients. Conclusion: Kabat therapy is very effective to improve the rehabilitation of Bell's Palsy patients if it is added to medical therapy or physical therapy.